Computational Technics. - Fattu, Nicholas A. (Review of Educational Research, 1951)
This article provides information on several computational techniques. Computational machines are generally classified either as digital or as analog computers. A digital device works with discrete values, and the results yielded are expressed in digits. An analog computer is one which numbers are converted into physically measurable quantities. In the automatic machine, sufficient instructions are given at the beginning to perform a whole complicated sequence of operations on many numbers without any outside assistance.